2016
DOI: 10.1002/jts.22102
|View full text |Cite
|
Sign up to set email alerts
|

Desired Involvement in Treatment Decisions Among Adults with PTSD Symptoms

Abstract: Virtually all respondents (97.3%) desired involvement in treatment decisions; two thirds (67.8%) wanted primary responsibility for decisions. Most (64.2%) wanted 30-60 minutes to learn about treatments and 80.1% wanted at least 1-3 days to consider their options. Respondents expressed more interest in informational content on treatment effectiveness and side effects than any other topic. In-person discussion with a provider was preferred more than other learning formats (e.g., websites, brochures). Results sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 43 publications
2
12
0
Order By: Relevance
“…Study participants ( N = 301) responded to online survey items that assessed demographics, treatment history, and preferences for treatment characteristics; these data have been published previously (Harik, Hundt, Bernardy, Norman, & Hamblen, 2016; Harik, Matteo, Hermann, & Hamblen, 2017). Using a computer‐generated 1:1 randomization procedure, participants were then randomly assigned to review descriptions of five first‐line PTSD interventions (PE, CPT, EMDR, SSRIs/SNRIs, and stress inoculation training [SIT]) either by reading sequential text descriptions of each treatment or by reviewing a comparison chart that included side‐by‐side information about each intervention.…”
Section: Methodsmentioning
confidence: 99%
“…Study participants ( N = 301) responded to online survey items that assessed demographics, treatment history, and preferences for treatment characteristics; these data have been published previously (Harik, Hundt, Bernardy, Norman, & Hamblen, 2016; Harik, Matteo, Hermann, & Hamblen, 2017). Using a computer‐generated 1:1 randomization procedure, participants were then randomly assigned to review descriptions of five first‐line PTSD interventions (PE, CPT, EMDR, SSRIs/SNRIs, and stress inoculation training [SIT]) either by reading sequential text descriptions of each treatment or by reviewing a comparison chart that included side‐by‐side information about each intervention.…”
Section: Methodsmentioning
confidence: 99%
“…The US Department of Veterans Affairs and US Department of Defense (2017) published clinical practice guidelines for the management of PTSD and acute stress disorder that encourages clinicians to use MW-centered and shared-decision making approaches that prioritize the MW's capabilities, needs, goals, and preferences. The findings of Harik et al (2016) support such guidelines; they found that individuals with symptoms of PTSD want to be involved in decisions regarding their care. It is concerning that the VHA is not able to adhere to these guidelines specific to MWs' overwhelming preference to receive treatment from a fellow MW.…”
Section: Retaining Eligible Mwsmentioning
confidence: 73%
“…With increased exposure to information about the treatments on the Clinical Practice Guideline site, individuals may feel more empowered to request the treatments that have the strongest research support, although this remains to be tested. In an online study of adults who screened positively for PTSD, participants were asked how much control over PTSD treatment decisions they would prefer: 23.6% reported wanting to make the decision themselves, and 44.2% reported wanting to make the final decision after taking the doctor’s opinion into account (Harik, Hundt, Bernardy, Norman, & Hamblen, 2016). If more than 60% of individuals with PTSD report wanting to ultimately choose their treatment, it seems that treatment providers should want to help them at least make informed treatment decisions.…”
Section: Discussionmentioning
confidence: 99%